1999
DOI: 10.2337/diabetes.48.10.1954
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of glucose hypersensitivity in beta-cells from normoglycemic, partially pancreatectomized mice.

Abstract: Increased ␤-cell sensitivity to glucose precedes the loss of glucose-induced insulin secretion in diabetic animals. Changes at the level of ␤-cell glucose sensor have been described in these situations, but it is not clear whether they fully account for the increased insulin secretion. Using a euglycemic-normolipidemic 60% pancreatectomized (60%-Px) mouse model, we have studied the ionic mechanisms responsible for increased ␤-cell glucose sensitivity. Two weeks after Px (Px14 group), Px mice maintained normogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
5
25
1
Order By: Relevance
“…Protein quantification using MagPix showed that the encapsulated UD hESCs expressed intracellular c-peptide (0.39 pg/mg total-protein) and glucagon (0.019 pg/mg total-protein). Although a previous study with primary mouse islets showed a c-peptide content of 9.93 ng/mg total-protein, 40 considering the present results are obtained with hESCs, this is indeed an encouraging step toward functional islet-like cell types from hESCs in 3D culture. Gene expression analysis showed that the required machinery necessary for glucose-stimulated insulin release was present by upregulation of the K ATP subunits SUR1 and KIR6.2 as well as glucokinase.…”
Section: Discussionsupporting
confidence: 54%
“…Protein quantification using MagPix showed that the encapsulated UD hESCs expressed intracellular c-peptide (0.39 pg/mg total-protein) and glucagon (0.019 pg/mg total-protein). Although a previous study with primary mouse islets showed a c-peptide content of 9.93 ng/mg total-protein, 40 considering the present results are obtained with hESCs, this is indeed an encouraging step toward functional islet-like cell types from hESCs in 3D culture. Gene expression analysis showed that the required machinery necessary for glucose-stimulated insulin release was present by upregulation of the K ATP subunits SUR1 and KIR6.2 as well as glucokinase.…”
Section: Discussionsupporting
confidence: 54%
“…However, the confounding effects of hyperglycemia in these models on BCM compensation, the signaling pathways, and ␤-cell gene expression could not be excluded (2). In contrast, the 60% Px rodent model offers a significant advantage in examining BCM compensation since a vigorous, but transient, regeneration process ensues despite a 60% reduction in BCM (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty percent Px was performed on 8-week-old male C57BL/6 mice (n ϭ 20 -25 per group) (Taconic), as described previously for rats (17) and mice (18). Mice were anesthetized with an intraperitoneal injection containing a mixture of ketamine (50 mg/kg) and xylazine (5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…It is thus possible that the sustained ␤-cell hyperactivity required to maintain normoglycemia in the face of insulin resistance, rather than hyperglycemia itself, leads to the observed changes in glucose sensitivity. The advantage of such a process is obvious as long as normoglycemia is preserved (42,49), but this physiological adaptation to increased insulin demands seems completely inoperative in the presence of persistent hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%